1933
DOI: 10.1002/path.1700370107
|View full text |Cite
|
Sign up to set email alerts
|

Multiple toxins produced by some organisms of the Cl. welchii group

Abstract: ALTHOUGH a n appreciable amount of research has been directed towards the study of the Cl. zvelchii group, the problem of the protection afforded by some antitoxic sera against certain toxins of other members of t h e group has not yet been adequately explained. I n 1928 Dalling (wide Mason Ross and Dalling 1931) stated that lamb dysentery antitoxic sera neutralised the toxin of Cl. welchii, but that the reverse did not hold good. Weinberg and Ginsbourg (1927) found however that perfringens (GI. welchii) anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

1940
1940
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…perfringens type C and some by type B, produce δ-toxin, which is one of the three extracellular hemolytic toxins that can be released, along with many other exotoxins and exoenzymes (Brooks, Stern, Warrack, 1957;Glenny et al, 1933;Oakley, Warrack, 1953;Orlans, Jones, 1958;Smith, 1979;Sterne, Warrack, 1964).…”
Section: Introductionmentioning
confidence: 99%
“…perfringens type C and some by type B, produce δ-toxin, which is one of the three extracellular hemolytic toxins that can be released, along with many other exotoxins and exoenzymes (Brooks, Stern, Warrack, 1957;Glenny et al, 1933;Oakley, Warrack, 1953;Orlans, Jones, 1958;Smith, 1979;Sterne, Warrack, 1964).…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1933 Glenny et al (2) reported that beta toxin was produced by Clostridium perfringens types B and C. This toxin was lethal, nonhemolytic, and elicited purplish, localized dermonecrosis following intracutaneous injection of depilated guinea pigs.…”
mentioning
confidence: 99%
“…Clostridium perfringens has been subdivided into six types : A to E distinguished by the production of one or more of the major lethal toxins a, p, 8 and L ; and F, which on the basis of toxin production would be included in type C, distinguished mainly by heat resistance, large cell size and epidemiology (Wilsdon, 1931 ;Glenny et al 1933 Zeissler & Rassfeld-Sternberg, 1949). Each of these types, including F, is further characterized by the production of a number of minor antigens, enzymic in nature, and distinguished by their effects on appropriate substrates and by the neutralization of these effects by the corresponding type antisera.…”
Section: Introductionmentioning
confidence: 99%